Incidence, characteristics, and long-term follow-up of sternoclavicular injuries: An epidemiologic analysis of 92 cases. Issue 2 (February 2016) - Boesmueller, Sandra; Wech, Margit; Tiefenboeck, Thomas M.; Popp, Domenik; Bukaty, Adam; Huf, Wolfgang; Fialka, Christian; Greitbauer, Manfred; Platzer, Patrick
Abstract : BACKGROUND: The majority of published studies concerning sternoclavicular injuries are case series or systematic reviews. Prospective studies on the subject are hindered by the low incidence of these lesions. The aims of the present study were to provide an overview of this rare entity compared with those described in the literature and to present the long-term clinical outcome. METHODS: We performed a retrospective data analysis of all sternoclavicular injuries treated at a single Level I trauma center from 1992 to 2011. Long-term clinical outcome was assessed using the ASES [American Shoulder and Elbow Surgeons], SST [Simple Shoulder Test], UCLA [University of California-Los Angeles] Shoulder Scale, and VAS [Visual Analog Scale] at latest follow-up. RESULTS: We detected an overall incidence of 0.9% of sternoclavicular injuries related to all shoulder-girdle lesions. Ninety-two patients (52 males and 40 females) with a mean (SD) age of 39.2 (19.5) years (median, 41 years; range, 4–92 years) were included in this study. The main trauma mechanism was fall. Classification was performed according to Allman, the time point of treatment after initial trauma, and the direction of the dislocation. Nine patients of the 15 Grade III lesions were treated conservatively by closed reduction and immobilization, while four patients were treated surgically by open reduction and internal fixation. Forty-nine percent of the patients were available for long-term follow-up at a median of 11.3 years (range, 5.3–22.6 years) with a mean ASES score of 96.21, SST score of 11.69, UCLA score of 31.89, and VAS score of 0.47. CONCLUSION: We found an overall incidence of 0.9% of sternoclavicular joint injuries related to all shoulder-girdle lesions and of 1.1% related to all dislocations, which is slightly lower compared with those described in the literature. Furthermore, we observed a high number of physeal sternoclavicular injuries with a percentage of 16% and overall good-to-excellent results at long-term follow-up. LEVEL OF EVIDENCE: Epidemiologic study, level IV.